Soluções de equações do 1º grau com duas variáveis, num contexto geométrico, com o auxílio do software Geogebra - Amadeu, Marcelo Bonfante (2023)
This work aims to carry out the study of the 1st degree equations with two variables, by using not only the algebraic context but also the understanding of the same in the geometric context, being this proposal developed by students of the 8th year of fundamental school, who will carry out seven activities, namely: 1st degree equations with two variables; Ordered pairs and their location in the Cartesian plane; Results of a 1st degree equation with two variables in the Cartesian plane; Solutions of a 1st degree equation with two variables; Systems of two linear equations with two unknowns; Problems with systems of 1st degree equations and Analysis of the different graphic resolutions of a system. The objective is to make the students understand the relationship of the algebraic expressions presented by interpreting the results obtained from them geometrically, so that they can improve the learning process, overcome their difficulties, be prepared and can achieve a better use in future situations involving the topic at hand. It is worth highlighting the use of the GeoGebra software by the students during most of the proposed activities. At times, 2nd degree algebraic expressions are presented with the intention that, when confronted with 1st degree algebraic expressions, they can perceive, when using the GeoGebra software, which graphic results are generated by each one of them, noticing their differences.